Environmentally Friendly Bioplastic Derived from Banana Peel (Musa paradisiaca) Waste and Agar-Agar Adhesive: An Experimental Study Employing a Completely Randomized Design (CRD) - Devikaduri, Laras; Handayani, Vitri Aprilla (JURNAL SINTAK, 2025)
This study aims to develop eco-friendly bioplastics from banana peel (Musa paradisiaca) waste with natural binder agar. The research employed a Completely Randomized Design (CRD) with one factor and three treatment levels of banana peel extract: 15 ml, 30 ml, and 45 ml. Each treatment was replicated three times, with three observed variables: tensile strength, maximum load, and water absorption. The analysis of variance showed that banana peel concentration significantly affected tensile strength and maximum load (p < 0.05), but not water absorption (p > 0.05). Further Duncan’s test indicated that the 30 ml treatment resulted in the best mechanical performance. These findings suggest that a formulation using 30 ml banana peel extract, 1 gram of agar, and 1 ml of glycerol can produce bioplastics with strong mechanical properties. This formulation holds potential as an environmentally friendly alternative to conventional plastics